Pengaruh Aplikasi Metode Drill Terhadap Ketrampilan Berbicara Bahasa Arab Siswa Kelas VIII MTS Wahid Hasyim Kapuran Badegan Ponorogo Tahun Pelajaran 2018/2019 - Amir Mukminin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2020)
Learning Arabic is very important because it discusses Muslims, the language of the Qur'an and Al-Hadith which is a guide to the life of Muslims. Therefore educational institutions also learn Arabic, so that * students can * understand Al-Qur'an and Al-Hadith as a source of Islamic law and teachings, so that they are good at speaking and composing especially in Arabic. Responding to this, in teaching and learning activities in an educational institution methods are needed precisely, so as to facilitate students' interest and enthusiasm for learning and can improve learning outcomes to the maximum. There are a number of methods teaching Arabic that can help students to easily understand the material conveyed by the teacher, especially Arabic material including the Drill method. By applying the Drill method it will affect the Arabic speaking ability of VIII grade students of Wahid Hasyim's MTs. With the formulation of the problem above, this study aims to determine the ability to speak Arabic and to determine the effect of the application of the Drill method on the ability to speak Arabic grade VIII students of MTs Wahid Hasyim Kapuran Badegan Ponorogo. In this study the authors used the Quantitative-Experimental research method, the data collection methods used were the test, observation, interview, and documentation methods. From the results of the data then analyzed using statistical formulas. The results of data processing using the one-way variant analysis formula or ANAVA, shows that there is an effect of the application of the .Drill Method to the ability to speak Arabic in VIII grade students of MTs Wahid Hasyim Kapuran Badegan Ponorogo.